SCALDED BUCKWHEAT MALT: PRODUCTION TECHNIQUE AND QUALITY EVALUATION - Tanashkina T.V.; Semenyuta A.A.; Boyarova M.D.; Klykov A.G. (Техника и технология пищевых производств)
Buckwheat is a promising raw material for malting. Different authors have shown that it can be used for production of gluten-freebottom and top fermentation beer, non-alcoholic beer, kvass, poly-malt extracts, bread improver and others. However, all researchers note buckwheat malt lack of solubility that makes its processing more difficult and entails additional costs. Scalding facili tates theimprovement of malt quality from cereal, though it has not been applied to buckwheat malt technology before. In th is study, threemodes were used to produce scalded malt from two buckwheat varieties (Izumrud and Pri 7). Its quality was evaluated in terms of moisture, extractability, amylolytic activity (diastatic power), Kolbach Index, amino nitrogen content, wort viscosity and acidity. Theregimes differed from one another by the duration of germination, duration and temperature of scalding as well. Following the firstmethod germination lasted for 2.5 days, and scalding for half a day at the temperature of 40 С. When using the second method germination lasted for 3 days and scalding for 1 day at the same temperature. The germination period of the third method was the same as for the second one but scalding took place at the temperature of 45 С. The results showed that scalding did not reduce amylolytic malt activity, contributed to a significant increase of extractability and amino nitrogen content in the wort, and the decrease of wort viscosity (except sample 3 of the Izumrud variety), and obtaining the optimum Kolbach Index. The most quality malt was produced using the third method, when grain was germinated during three days and then it was exposed to scalding at the temperature o f 45 С for one day. Variety differences were observed in terms of malt extractability. It was higher for the Pri 7 variety. The other character- istics did not differ essentially. Scalded malt can be recommended for production of fermented beverages, mass consumption fo ods and specialized foodstuffs.